2020
DOI: 10.1177/0391398819899669
|View full text |Cite
|
Sign up to set email alerts
|

Differences in predicting glucose absorption from peritoneal dialysate compared to measured absorption in peritoneal dialysis patients treated by continuous ambulatory peritoneal dialysis and ambulatory peritoneal dialysis cyclers

Abstract: Background and aims: Glucose-containing peritoneal dialysates are used to generate an osmotic gradient for the convective removal of water and sodium. Predictive equations were developed to estimate glucose absorption without having to formally measure changes in dialysate glucose. In view of the changes in peritoneal dialysis prescriptions over time, we compared predicted and measured glucose absorption. Subjects/methods: We measured peritoneal glucose losses when peritoneal dialysis patients attended their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The two groups had been treated with PD for a similar duration, and had a similar number of diabetics, blood glucose, glycated hemoglobin, serum albumin, and C‐reactive protein. Although more patients treated with dual chamber low GDP dialysates used CCPD, both glucose exposure and measured glucose absorption from the peritoneal dialysates were not different 17 …”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The two groups had been treated with PD for a similar duration, and had a similar number of diabetics, blood glucose, glycated hemoglobin, serum albumin, and C‐reactive protein. Although more patients treated with dual chamber low GDP dialysates used CCPD, both glucose exposure and measured glucose absorption from the peritoneal dialysates were not different 17 …”
Section: Discussionmentioning
confidence: 85%
“…Although more patients treated with dual chamber low GDP dialysates used CCPD, both glucose exposure and measured glucose absorption from the peritoneal dialysates were not different. 17 Our study included many more patients, and patients had been treated for a similar time with PD, whereas in the earlier positive report, patients using the standard single chamber dialysates had been treated for a median of 102 months compared to 44 for those using dual chamber low GDP dialysates. 24,25 Note: Data expressed as mean ± standard deviation, and median (inter-quartile range).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, on multivariable analysis, we also found that apart from ultrafiltration, those patients with increased ECW/TBW ratio had relatively lower peritoneal sodium removal to glucose absorption, suggesting that a lower sodium removal to glucose absorption is associated with increasing ECW/TBW, [25] which may lead to ultrafiltration failure and transfer from PD. In addition, simply increasing the glucose dialysate usage risks increasing glucose absorption, [32] and excess fat weight gain. [33] So early identification of patients with a low dialysate sodium removal to glucose absorption ratio, would potentially allow targeted dietary or change of PD modality in those at greater risk of ECW overload and fat weight gain, and maintaining patients on PD.…”
Section: Discussionmentioning
confidence: 99%